Una guerra italiana combattuta a Parigi: Bontempelli, “900” e i suoi avversari - Gennaro, Rosario (Incontri. Rivista europea di studi italiani, 2020)
An Italian war fought in Paris Bontempelli, “900” and its opponents “900”, directed by Massimo Bontempelli, was a French language journal published in Italy from 1926 to 1928. It had an international editing committee. This included exponents of Parisian “modernism”. Bontempelli wished to use the journal as a means to create a broad base of contacts in the French capital to create the conditions for his international literary legitimation. The journal’s publishing company was under Fascist control since Mussolini’s regime was promoting a policy referred to as “cultural expansion”. The aim of this policy was to increase the international influence of Italy via the spread of its culture. Since the French capital was the centre of international culture, Paris became an important destination of this “cultural expansion”. Bontempelli became an integral part of this policy, as he was in touch with the intellectuals and journals forming a part of it. “900” was therefore proposed as a journal created to spread Italian culture to Paris. However, it could not openly adopt the use of imperialist or nationalist language in order not to upset the collaborators in Paris. The Italian adversaries profited from this contradiction to fight Bontempelli and accused him of playing a double game in the eyes of Italian and French supporters. The disputes around the journal “900” thus concerned the relationship with Paris, but also involved above all players and motivations of the Italian literary scene.